PLC-CONTROLLED OF A CONVEYOR SYSTEM (SYSTEM III) - IDRIS, ADRIEN MUHAMMAD BIN (Universiti Teknologi PETRONAS, 2012)
This project entitled PLC-Controlled of a Conveyor System (System III), which is an integrated system that is operated and controlled by the PLC used itself. A project that made to study the capabilities of the conveyor system installed in one of UTP’s laboratory. Besides that, this project also requires study for developing the set of PLC programming routines using structured method as to allow the modifications of the system operation that is proper and preferable. This system has been rarely used and only operated for the demonstration purposes, which lead to the inflexibility of the system. In addition, none of work to develop and understand the system’s programming routines ever conducted which also cause no research activities made for quite some time. As a solution, the study to develop the programming routines for the system through structured method is implemented. This method is a step-by-step method to develop the PLC programming routines using ladder diagram, which begins with the program description, to the timing / sequence diagram until the PLC ladder diagram is developed. Based on this method, the system capabilities can be studied in details and the system operation is successfully being modified along the project is conducted. In conclusion, the project was successful, and in future it is believed the development of PLC programming routines could be easily done for advance or complex operation. The system also could be improved to cope with the modern technological growth in the Flexible Manufacturing System (FMS) field, as well to assist the possible project and research activities later.